1991
DOI: 10.1111/j.1468-5914.1991.tb00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Systems of Interpretation and the Function of Metaphor

Abstract: Metaphor is the subject of a diverse literature (cf. Honeck & Hoffman, 1980; Ortony, 197913;Sacks, 1979) that often juxtaposes views from different areas of inquiry, attending little to their implications for other areas. These views frequently emphasize structural features of a delimited expression taken to be metaphorical, giving only secondary consideration to the functions, purposes, or uses of the expression. This paper reverses these practices by emphasizing the uses of metaphors in their social context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Metaphors can offer new ways of looking at existing situations (Crider and Cirillo, 1991;Lakoff, 1990;Morgan, 1980Morgan, , 1983, while simultaneously acting as a bridge from a familiar to a new state (Pondy, 1983). The high latitude of interpretation afforded by metaphorical statements can help to accommodate the interpretations of organizational groups perceiving their interests to be mutually incompatible (Crider and Cirillo, 1991), and unstructured situations can be made more concrete and comprehensible through the use of metaphor (Sackmann, 1989). Researchers have shown that the metaphors used by organizational actors are empirically related to such areas as the extent and speed of organizational change (Oswick and Montgomery, 1999) or to aspects of organizational and national culture (Gibson and ZellmerBruhn, 2001).…”
Section: How Metaphor Can Foster Effective Organizational Changementioning
confidence: 99%
“…Metaphors can offer new ways of looking at existing situations (Crider and Cirillo, 1991;Lakoff, 1990;Morgan, 1980Morgan, , 1983, while simultaneously acting as a bridge from a familiar to a new state (Pondy, 1983). The high latitude of interpretation afforded by metaphorical statements can help to accommodate the interpretations of organizational groups perceiving their interests to be mutually incompatible (Crider and Cirillo, 1991), and unstructured situations can be made more concrete and comprehensible through the use of metaphor (Sackmann, 1989). Researchers have shown that the metaphors used by organizational actors are empirically related to such areas as the extent and speed of organizational change (Oswick and Montgomery, 1999) or to aspects of organizational and national culture (Gibson and ZellmerBruhn, 2001).…”
Section: How Metaphor Can Foster Effective Organizational Changementioning
confidence: 99%
“…From this perspective, metaphor serves a function less easily expressed, or even inexpressible, in literal language (see Crider & Cirillo, 1989;Olson, 1988). Other functions of metaphor and other tropes have revolved around the social functions of figurative language use (see Crider & Cirillo, 1989;Furnham, 1987;Gerrig & Gibbs, 1988). From this perspective, figurative language serves to express socially relevant information such as intimacy, attributions, attitudes, and beliefs and may interact with metacognition about the vividness or persuasiveness of different types of messages.…”
Section: Why Do We Use Metaphor and Other Forms Of Figurative Language?mentioning
confidence: 96%
“…Wheelwright (1962), Ortony (1975), and others have made the claim that at least some instances of metaphor can serve an expository function not served by literal language, especially when dealing with creative thought. From this perspective, metaphor serves a function less easily expressed, or even inexpressible, in literal language (see Crider & Cirillo, 1989;Olson, 1988). Other functions of metaphor and other tropes have revolved around the social functions of figurative language use (see Crider & Cirillo, 1989;Furnham, 1987;Gerrig & Gibbs, 1988).…”
Section: Why Do We Use Metaphor and Other Forms Of Figurative Language?mentioning
confidence: 97%
“…Studies from an interpretive perspective have illustrated how language used as a symbolic process is central to the development and sustainment of shared meanings (Smircich, 1983) and a common identity for organizational members (Evered, 1983). The guiding motivation of the approach is to gain an in-depth understanding of the role of language in meaning construction processes and to this end researchers have explored such elements or configurations of discourse as stories (Martin & Powers, 1983;Boje, 1991;Hansen & Kahnweiler, 1993;Boyce, 1995), humor (Rodrigues & Collinson, 1995;Hatch, 1997), and metaphor (Crider & Cirillo, 1991;Tsoukas, 1991Tsoukas, , 1993Chilton & Ilyin, 1993).…”
Section: The Interpretive Approach: Discourse As Constructive Of Socimentioning
confidence: 99%